Impacts of sheep grazing on soil properties and growth of rubber (Hevea brasiliensis) - Nik Ab. Majid, Nik Muhamad; Awang, Kamis; Jusoff, Kamaruzaman (1987)
The agronomic and economic importance of sheep grazing is receiving increased attention in rubber plantations in Malaysia. Measurements of soil physical and chemical properties, foliar and tree girth of rubber (Hevea brasiliensis) in a Rubber Industry Smallholders Development Authority (RISDA) mini-estate at Bukit Mahang, Ketereh in Kelantan showed 15 months of grazing did not cause serious soil compaction to restrict water movement into and through the soil profile especially during intense rainstorms. All measurement of soil physical properties, namely soil moisture content, particle density, bulk density, total pore space, macropores, micropores, saturated hydraulic conductivity, soil temperature, particle-size distribution, loss on ignition and resistance to root penetration indicated an aggradation at the soil surface (0-10 cm depth) due to grazing. However, except for K, the other soil nutrients namely total N,P,Ca and Mg levels and soil pH under grazing were greater in relation to ungrazed area. Foliar analysis showed that N,P,Ca, Mg and Na increased with grazing. Potassium, however, decreased with grazing. Trees under grazing have higher girth increment than ungrazed area. The understanding of these parameters will allow proper agroforestry management practices to be adopted in rubber plantations.